Determinants Influencing QRIS Adoption as a Digital Payment Tool in Ciledug, Tangerang City - Andi Amri; Rahmi Fitria Malik; Muhammad Kemal Fachrandi (Airlangga Journal of Innovation Management, 2025)
This study aims to determine the effect of perceived usefulness, perceived trust, and community preferences on decisions to use QRIS in Ciledug sub-district, Tangerang City. This study uses quantitative methods with a causality approach, and the sampling technique is purposive sampling with a sample size of 100 people. The findings show, that the t-test results of perceived usefulness have a t-count value of 1.159 with Sig 0.249> 0.05, which means there is no significant influence between perceived usefulness and the decision to use QRIS. Furthermore, perceived trust with a t-count value of 2.218 with Sig 0.029 0.05, means that there is a significant influence on trust preferences in using QRIS. Then people's preferences obtained a t-count value of 1.842 with Sig 0.069> 0.05, which means there is no effect of people's preferences on using QRIS as a digital payment tool. While simultaneously there is a significant influence between perceived usefulness, perceived confidence, and community preferences on the decision to use QRIS. This means that the level of influence of each variable studied is still low. This research could become a reference for the Ciledug community, especially for local leaders and banks to increase public interest in to use of QRIS as a digital payment tool.